FOXF2 inhibits proliferation, migration, and invasion of Hela cells by regulating Wnt signaling pathway. Issue 5 (17th October 2018) - Zhang, Jun; Zhang, Chunxia; Sang, Lin; Huang, Ling; Du, Juan; Zhao, Xingbo
Abstract : This article was aimed to study the FOXF2 effects on cervical cancer. Tumor tissues and adjacent tissues of 41 cervical cancer patients were collected. Human endometrial epithelial cells (hEEC) and Hela cells were cultured. FOXF2 expression vector and its empty vector were transfected into Hela cells, and named as pcDNA 3.1-FOXF2 group and Vector group, respectively. Hela cells without any treatment were set as Blank group. qRT-PCR was used to detect mRNA expression. Nude mouse xenograft assay was performed to test Hela cells proliferation ability in vivo . FOXF2 and β-catenin positive cell numbers were detected by immunohistochemistry. Protein expression was analyzed by Western blot. Cells migration and invasion were conducted by Transwell. Tumor tissues and Hela cells FOXF2 expression were lower than that in adjacent tissues and hEEC ( P <0.01). Low FOXF2 expression predicted poor outcomes of cervical cancer patients. Compared with Blank group and Vector group, Hela cells of pcDNA 3.1-FOXF2 group were with higher FOXF2 expression, lower OD495 value, migrated and invaded cells, higher E-cadherin expression, lower Vimentin and Snail expression, smaller tumor volume in nude mice, lower c-Myc, CyclinDl, MMP9, Lgr5, and nuclear β-catenin expression (all P <0.01). FOXF2 inhibits Hela cells proliferation, migration, and invasion through regulating Wnt signaling pathway.